Ataxia telangiectasia in a Bahraini child treated with intensive physiotherapy: A case report - Fatima Razzaqi; Aysha Albastaki; Israa Sinan (Hong Kong Physiotherapy Journal)
Ataxia telangiectasia (AT) is a rare neurodegenerative condition with a prevalence of 1 in 40,000 to 1 in 300,000 worldwide. It involves a genetic mutation of chromosome 11q.26. The condition is inherited in an autosomal recessive manner causing atrophy of the cerebellum due to loss of Purkinje fibres. AT presents early in childhood and the clinical features depend on the type of mutation. The study is a case report of a rare genetic disorder of a 9-year-old female who came to the physiotherapy clinic with a diagnosis of AT. The patient was presented with progressively worsening gait problems with frequent falls, with complete dependence on assistance and impaired balance and coordination. The treatment program was 12 months divided into an intense physiotherapy program for two months followed by 10 months of two times per week of physiotherapy sessions. The program was divided into four elements which are: (1) Lifestyle changes, (2) Strengthening exercises, (3) Coordination exercises, and (4) Balance training exercises. The result showed a positive outcome in increasing the patient’s independence, increased muscle strength, reduced ataxia symptoms intensity, and the patient can carry out complex activities with the help of accessory orthosis devices.